Media Exposure Regarding Terrorist Events And Posttraumatic Stress Disorder In Youth - Shahzad, Sobia; Rashid, Abbas (2015)
Throughout its history Pakistani citizens are bearing the losses resulting from terrorism. After 9/11, 2001, there is a rise in suicide attacks on public places in Pakistan especially in major cities. Media give massive coverage to these attacks and highlight all aspects in detail which create a great sense of fear in general public particularly in youth. These threats and fears can become serious psychological problems if not met with proper treatment. In this experimental study of media exposure regarding terrorist events and posttraumatic stress disorder in youth, depression level and posttraumatic stress disorder are assessed by using intervention among the 150 undergraduate students of three universities of Faisalabad, using the technique of cluster sampling. “Self-rating Inventory Posttraumatic Stress Disorder of 22 items” and Beck’s Inventory Depression were used to measure the posttraumatic Stress Disorder in students. It showed 79% reliability while inter-items reliability was observed .807. Before using the intervention Mean score of Total Pretest Posttraumatic Stress Disorder was 14.31 which increased after intervention (14.86 - 14.32) = .54. It means there was significant psychological effect of exposure of terrorist events , which is really a sign of contemplate for media policy makers, owners and practitioners for telecasting terrorist event on screen because the psychiatrists recommend the prescription and coping strategies if the person score 10 on the Self-rating Inventory for Posttraumatic Stress Disorder. The findings also reveals that the total mean score of Posttraumatic Stress Disorder after intervention was 15.89 in female students which was higher than male students 13.96. Beck’s Inventory Depression finds that the depression among female undergraduate students was higher than male undergraduate students after the usage of intervention. Both posttraumatic Stress Disorder and depression increase after the exposure of terrorist events which is a point of serious concern for media monitors in Pakistan.